Peran Konten Mukbang dalam Membentuk Ketergantungan Makan Sambil Menonton: Perspektif Teori Dependensi Media - Sidi, Pandu Bintang; Viandra, Syifa Chairunnisa; Amran, Sri Oktika; Triyandra, Annisa Citra (LITERAKOM: Jurnal Literasi dan Komunikasi, 2024)
Media has become an inseparable staple in people's lives. Its presence has expanded to become an inseparable part of our daily routine. Therefore, people will be very dependent on the use of media. New media was born from today's technological advancements and gave rise to various types of new media in communication, one of which is YouTube. YouTube is a very famous platform for video sharing where users can upload, watch and share videos free of charge. One trend that is gaining popularity among many people is watching others eat through broadcasts known as mukbang. There is also a lot of enthusiasm for this content, this happens because it displays appetizing food, thus impacting affective changes in its audience, giving a long-term effect to continue watching it.